Pharmaceuticals in the Environment : sources, fate, effects, and risks - Kèummerer, Klaus (Springer, 2017)
Following the success of the first edition, this pioneering study of pharmaceuticals in the environment has been updated and greatly extended. It includes the status of research on pharmaceuticals in soil, with attention to terrestrial and aquatic environments as well as new substance categories such as tetracylines and chinolones and the latest results concerning contamination of the environment and risk reduction.